Profile of Mother's Knowledge and Behavior Toward Stimulation and Their Babies' Development in an Urban Poor Area in Jakarta - Titi S. Sularyo; Ulynar Marpaung; Arwin A. P. Akib (Indonesian Pediatric Society, 1999)
This was a field study carried out in all Posyandus located in Pulo Gadung, a poor urban of East Jakarta, from April until October 1998. Three hundred and fourteen mothers and their babies were recruited. Most of the mothers (67.2%) aged from 20-29 years old, with low education level (42.4%) and a low income (19.4%). Almost all respondents were housewives and the average number of children was two (34.7%). The most important source of information for the respondents was the electronic media. Almost half of mothers behaved well toward stimulation of their babies development (49.4%); however, 64.3% had low knowledge especially about the time baby could sit upright with a good head control. Those who behaved fairly and poorly comprised 35.7% and 15%, respectively. It seems that fine motor sector was neglected. There was no significant association between mother’s knowledge and behavior towards stimulation and the development of their respective babies (p<0.5722). It revealed also that the income per capita had significant association with development of the babies (p=0.033).